Key technologies in collaborative network based on MEC - Xiaoting MA; Junhui ZHAO; Xiaoke SUN; Yi GONG (Dianxin kexue)
In order to solve the performance degration problem of low latency and high reliability caused by the high-speed mobility of vehicles,the key technologies of collaborative network based on MEC (mobile edge computing) were studied.Starting from the uniqueness of MEC in vehicular networks,the collaborative networking scheme with low latency and high reliability was introduced.According to the two most promising cooperative scenarios of vehicle platooning and UAV (unmanned aerial vehicle) assisted communication in 5G vehicular networks,the key technologies of cooperative resource management based on MEC were investigated.In addition,the research direction analysis of resource management based on MEC in vehicular networks provides a reference for further study.